The academic administrator grid - Blake, Robert R.; Mouton, Jane Srygley; Williams, Martha Shipe (San Francisco : Jossey-Bass, 1981)
Vols. 2, 4-11, 62-<68> include the Society's Membership list; v. 55-80 include the Journal of applied mechanics (also issued separately) as contributions from the Society's Applied Mechanics Division
Includes index.
Bibliography : p. 389-411.
Keywords: Universities and colleges -- Administration; School administrators; Management